2021
DOI: 10.3390/s21051707
|View full text |Cite
|
Sign up to set email alerts
|

ZARATAMAP: Noise Characterization in the Scope of a Smart City through a Low Cost and Mobile Electronic Embedded System

Abstract: Like other sources of pollution, noise is considered to be one of the main concerns of citizens, due to its invisibility and the potential harm it can cause. Noise pollution could be considered as one of the biggest quality-of-life concerns for urban residents in big cities, mainly due to the high levels of noise to which they may be exposed. Such levels have proven effects on health, such as: sleep disruption, hypertension, heart disease, and hearing loss. In a scenario where the number of people concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Based on the RMP analysis theory, this research is designed to collect data from three aspects: resource analysis, tourism market analysis, and adaptive reuse analysis. Among them, cultural elements, activation of tourism A variety of quantitative analysis methods are used to study the activation of tourism cultural and creative projects in traditional blocks of Wudian city from a quantitative perspective [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the RMP analysis theory, this research is designed to collect data from three aspects: resource analysis, tourism market analysis, and adaptive reuse analysis. Among them, cultural elements, activation of tourism A variety of quantitative analysis methods are used to study the activation of tourism cultural and creative projects in traditional blocks of Wudian city from a quantitative perspective [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…The post hoc ANOVA test (Table 1) was compared to obtain significant results and the results were similar to those of [1,7]. Site 1 is a ring road, site 2 is a construction area and site 3 is an industrial area.…”
Section: Daily Variancementioning
confidence: 91%
“…Motion activity (9 Degree of Freedom(DoF)) motion tracking by accelerometer, gyroscope and magnetometer. Indoor/Outdoor Wrist-worn devices can integrate parameters from the environmental, behavioral, and physiological domain [ 80 ] Noise level [db] Outdoor The main function of the proposed study is to provide an example of real-time information on the acoustic impact on the city. This work is currently in progress at this stage of the project so that calibration and adjustment of the final acoustic sensor can be carried out [ 81 ] Ambient sound level (PONG) Air quality: VOC and NO 2 .…”
Section: Table A1mentioning
confidence: 99%
“…In [79], the authors demonstrated the feasibility of collecting personal Particulate Matter (PM2.5), language, noise data, cognitive assessments, and biospecimens from a sample of 3-4-yearold children using wearable ultrafine particle sensors and LENA-Language Environment Analysis System. Two different approaches were then collected to provide an example of real-time information on urban acoustic pollution [80] and overall personal pollution [81], where the PONG device can monitor ambient sound levels as well as VOCs and NO 2 , UVA and UVB, air temperature, relative humidity and air pressure data.…”
Section: Monitoring Of Acoustic Ef With Wearablesmentioning
confidence: 99%